EVALUASI PEMBELAJARAN FIKIH PADA PENDIDIKAN MADRASAH IBTIDAIYAH (MI) - Juanda Sikumbang (Jurnal Al-Fatih, 2021)
An important aspect of learning is evaluation. Jurisprudence learning at Madrasah Ibtidaiyah is one of the PAI lessons that study religious fiqh which concerns understanding the ways of implementing the pillars of Islam and their implementation in everyday life. The purpose of this article is to describe the principles of Jurisprudence assessment, the Jurisprudence evaluation technique in MI, the Jurisprudence Assessment Instrument in MI, Processing and Reporting of the Jurisprudence Evaluation Results in MI. This research method is library research method. The results of this study are: the objectives of fiqh learning for Madrasah Ibtidaiyah are emphasized on knowledge, experience, and habituation of the simple implementation of Islamic law in the form of worship and daily behavior as well as the provision of subsequent education. Jurisprudence evaluation and assessment techniques at Madrasah Ibtidaiyah for all basic competencies include attitude (affective), knowledge (cognitive) and skills (prikomotor). The principle of learning assessment can be said to be carried out well if the implementation adheres to three principles, namely: a) Overall principles; b) The principle of sustainability; c) The principle of objectivity. Broadly speaking, there are two parts of evaluation techniques that educators can use in finding the necessary information, namely: Tests and Non-tests. In this non-test, evaluation techniques include: Ratting; Quastionaires; Interview; Observation; Documentation.